Genes and physical fitness - Gronek, Piotr; Holdys, Joanna (Akademia Wychowania Fizycznego w Poznaniu)
The search for genes with that positively affect physical fitness is a difficult process. Physical fitness is determined by numerous genes, and its genetic determinants are modified by environmental factors. The map of candidate genes that can potentially affect physical fitness becomes larger every year, and currently it contains more than 200 genes associated with such aspects as respiratory and cardiovascular stability; body build and composition – especially muscle mass and strength; carbohydrate and lipid metabolism; response to training; and exercise intolerance. The inclusion of the genetic component in physiological and biochemical studies would permit drawing a representation of predispositions for each athlete interested in practicing high performance sports and would be a valuable coaching aid in the process of training individualization.
Keywords: genes; physical fitness